Arteriovenous fistula and high output cardiac failure in a double lung transplant patient. Issue 8 (28th August 2019) - Bennitz, Joshua; Simons, Martin; Lorello, Gianni R
Abstract : We present a case of a high cardiac output (CO) arteriovenous fistula (AVF) with pulmonary hypertension (PH) post-double lung transplant presenting for AVF occlusion. The patient presented with a CO of 9.83 L/min, pulmonary artery pressures of 64/16, inferior vena cava dilatation and an AVF between the left common iliac artery and vein. Given her anaesthetic considerations, we elected to proceed with local anaesthesia and sedation. Trial balloon occlusion resulted in an increase in blood pressure and a headache that resolved with balloon deflation. Successful final occlusion with an endovascular stent was completed without adverse events. PH is a complex pathophysiology with the potential for catastrophic decompensation. Anaesthesiologists must consider a patient's comorbidities and the procedure to safely administer anaesthesia without complications.